Numerical Investigation of Clocking Effect on Fluctuating Characters and Radial Force within Impeller for a Centrifugal Pump - X. Zhu; X. Han; C. Xie; H. Zhang; E. Jiang (Journal of Applied Fluid Mechanics, 2025)
The present work aims to investigate the influence of vane clocking effect on fluctuating characters and radial force on impeller for centrifugal pump. Numerical simulations were conducted with validation by experiments, at four different relative angular position between vane and tongue. The power consumption and work done by blades are evaluated in time-history. The radial velocity, circumferential velocity at impeller-diffuser clearance is depicted by expanding the turning surface, for comparison under different diffuser position to reveal the flow distortion affected by clocking effect. The results indicate that when vane trailing edge is at tongue (θd1), the corresponding diffuser channel is placed against small flow section in volute leading to a blocking effect that results in significant circumferential inhomogeneity at diffuser outlet. The interaction between impeller blade and different diffuser vane presents distinct intensity, causing the unsteady fluctuation intensity of power consumption of impeller at different vane positions is significantly different, and so is the radial force. As the diffuser vane moves away from tongue (at θd4), the blocking effect reduces and the flow field becomes more evenly distributed among each channel. Resulting in weaker fluctuations in the power consumption, blade load and radial force.